The sum of the exponents

Algebra Level 2

Find the sum of all real numbers x x satisfying the equation

2 x + 3 x 4 x + 6 x 9 x = 1 2^x + 3^x - 4^x + 6^x - 9^x = 1 .


The answer is 0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Saurabh Mallik
Apr 13, 2014

There is only 1 1 possible value of x x , that is 0 0 .

Sum of real numbers satisfying x x in the equation = 0 \boxed{0}

I didn't get this part how can you say that there is only one possible value of x.

Nischay Mandal - 7 years, 1 month ago

Log in to reply

well, in that case; just try and put any other value of x which satisfies the equation :P

Sparsh Jain - 7 years, 1 month ago

Log in to reply

Well i'm afraid this is NOT a logical assumption.

Jimmy Pham Hoang Nhat - 7 years, 1 month ago

Do you think that you are answering logically

Nischay Mandal - 7 years, 1 month ago

How can it be solved theoretically without trial and error method Can anyone explain with steps?

Kartikeyan Litlle Dhoni - 7 years, 1 month ago

Log in to reply

Draw the graph and see..

Gabriel Lefundes - 7 years, 1 month ago
Sharky Kesa
Jan 28, 2017

Let a = 2 x a=2^x , b = 3 x b=3^x , c = 1 x c=1^x . We have

a c + b c a 2 + a b b 2 = c 2 a 2 + b 2 + c 2 a b b c c a = 0 2 a 2 + 2 b 2 + 2 c 2 2 a b 2 b c 2 c a = 0 ( a b ) 2 + ( b c ) 2 + ( c a ) 2 = 0 \begin{aligned} ac + bc - a^2 + ab - b^2 &= c^2\\ a^2 + b^2 + c^2 - ab - bc - ca &= 0\\ 2a^2 + 2b^2 + 2c^2 - 2ab - 2bc - 2ca &= 0\\ (a-b)^2 + (b-c)^2 + (c-a)^2 &=0\\ \end{aligned}

Since squares are non-negative, we must have each of the three squares equal to 0. Thus, a = b = c a=b=c so 2 x = 3 x = 1 x = 1 2^x = 3^x = 1^x = 1 so x = 0 x=0 .

Komal Vasudeva
Jan 28, 2017

Split the terms as : 4 x = 2 x 2 x 4^{x} = 2^{x} * 2^{x} , 9 x 9^{x} as 3 x 3 x 3^{x} * 3^{x} , 6 x 6^{x} as 2 x 3 x . 2^{x}* 3^{x}. , and so on .. Take 3 x = a 3^{x}=a , 2 x = b 2^{x}= b , 1 x = c , 1^{x} =c , then a 2 + b 2 + c 2 a^{2} + b^{2} + c^{2} = ab+ bc + ca . The eqn. has one sol. with a= b= c= 1. Hence 2 x = 3 x = 1 2^{x} = 3^{x} =1 So. x = 0 . x=\boxed{0}.

You almost got it! I forgot about this question. I'll post the answer.

Sharky Kesa - 4 years, 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...